2007
DOI: 10.1159/000103869
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Neck Structures after Supracricoid Partial Laryngectomy: A Multislice Computed Tomography Evaluation

Abstract: Background: Surgery of laryngeal cancer used to profoundly alter the anatomy of the cervical region. Accurate anatomo-embryologic studies and repeated surgical trials allowed recognition of the cricoarytenoid complex as the smallest anatomofunctional unit able to maintain all the laryngeal functions. Objectives: The aim of this study was to determine whether significant variations of neck anatomical parameters exist after partial laryngectomy, and to analyze whether some of these parameters are associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(7 reference statements)
0
3
0
Order By: Relevance
“…Why was OSA more severe in the PVL patients when compared to individuals offered PHL? CT scans of the larynx taken in the late postoperative follow-up of partial horizontal laryngectomy patients indicate the size of the cricoid cartilage ring remained unaltered 14 . There is little material of soft tissue density in the lumen of the cricoid ring after PHL 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Why was OSA more severe in the PVL patients when compared to individuals offered PHL? CT scans of the larynx taken in the late postoperative follow-up of partial horizontal laryngectomy patients indicate the size of the cricoid cartilage ring remained unaltered 14 . There is little material of soft tissue density in the lumen of the cricoid ring after PHL 15 .…”
Section: Discussionmentioning
confidence: 99%
“…However, both these methods allow only two-dimensional observation. Because of the altered configuration of the neoglottis, three-dimensional evaluation is superior to two-dimensional observation methods 12 . The present study used our previously reported three-dimensional reconstruction techniques to further explore the three-dimensional morphology of the neoglottis, in additional cases 7 …”
Section: Discussionmentioning
confidence: 99%
“…12 The present study used our previously reported three-dimensional reconstruction techniques to further explore the three-dimensional morphology of the neoglottis, in additional cases. 7 Mean linear distance measurements demonstrated sufficient movement in both bilateral and unilateral arytenoids.…”
Section: Figmentioning
confidence: 99%